Fundamental studies of the adhesion of explosives to textile and non-textile surfaces - Yu, H.; Becker, Thomas; Nic Daeid, N.; Lewis, Simon (Elsevier Ireland Ltd, 2017)
This paper describes the use of atomic force microscopy (AFM) to investigate the interactions between explosives crystals and different surfaces. Crystals of TNT, PETN and RDX were mounted onto tipless AFM cantilevers and repeatedly brought into contact with a range of surfaces (n = 15), including textile and non-textile surfaces. The adhesion force during each contact was measured, and the results are presented in this work. The results suggest that explosives crystals display a higher adhesion to smoother, non-textile surfaces, particularly glass. This finding may be of use for forensic explosives investigators when deciding the best types of debris to target for explosives recovery.